Speech Act Analysis of the Formality Scale of Digestive Surgeon Specialist - Salwa Pramesti Maharani (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: In this study, the formality scale speaking behaviors of digestive surgeons to patients were explained. Using reflective and descriptive notes to gather data for this research. To evaluate whether the utterances were included in the speech act coding that characterizes the formality scale, the researcher conducted a heuristic analysis of the data. The research data is spoken conversational language between physicians and patients at Abdul Moeloek Hospital in Bandar Lampung that depicts the degree of formality (formal and informal) as a setting for creating relationships. Keywords: discourse analysis, formality scale, speech acts.